GABA/glutamate co-release controls habenula output and is modified by antidepressant treatment - Shabel, Steven J. (2014)
The lateral habenula (LHb), a key regulator of monoaminergic brain regions, is activated by negatively valenced events. Its hyperactivity is associated with depression. Although enhanced excitatory input to the LHb has been linked to depression, little is known about inhibitory transmission. We discovered that γ-aminobutyric acid (GABA) is co-released with its functional opponent, glutamate, from long-range basal ganglia inputs (which signal negative events) to limit LHb activity in rodents. At this synapse, the balance of GABA/glutamate signaling is shifted toward reduced GABA in a model of depression and increased GABA by antidepressant treatment. GABA and glutamate co-release therefore controls LHb activity, and regulation of this form of transmission may be important for determining the effect of negative life events on mood and behavior.